Efektivitas Bahan Alami dalam Meningkatkan Jumlah Sel Fibroblas pada Soket Gigi Tikus Wistar Setelah Pencabutan Gigi - Muhammad Fajrin Wijaya; Aditya H. Asmara; Indrya Kirana Mattulada; Andy Fairuz Zuraida Eva; Andi Fajrin Perdana Sam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The healing process of a tooth socket after extraction involves various stages, including the proliferation of fibroblasts that play a role in the formation of new tissue. Natural ingredients have long been used in accelerating wound healing, but their effectiveness in increasing the number of fibroblast cells still needs to be studied further. To determine the effectiveness of natural ingredients in increasing the number of fibroblast cells in the tooth socket of Wistar rats after tooth extraction. Methods: This is a literature review that collects and analyzes scientific articles from various databases such as PubMed, Google Scholar, DOAJ, Garuda Portal, and CrossRef. The selected articles met the predetermined inclusion criteria, including studies conducted on Wistar rats and using natural ingredients as interventions. Red ginger extract at 10% concentration was found to be the most effective ingredient in increasing the number of fibroblasts and accelerating wound healing. Red ginger extract (Zingiber officinale var. rubrum) is the most effective natural ingredient in increasing the number of fibroblast cells in the tooth socket of Wistar rats after tooth extraction.